Large catches of beluga whales in Godthåb (Nuuk). Postcard : Stor fangst af hvidhvaler ved Godthåb. Postkort - Unknown (University of Southern California Digital Library (USC.DL), 2015)
Large catches of beluga whales in Godthåb (Nuuk). Postcard